The Legitimacy of Migrant Preachers in Community Empowerment in Bengkulu City, Indonesia - Rahmat Ramdhani; Rohimin; Aan Supian; Ridho Syabibi; Sultan Gholand Astapala; Abdulloh Hadziq (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
The research begins with the existence and role of migrant Da`I in da'wah activities in the city of Bengkulu; their existence is accepted by the community despite the differences in language and culture. In addition to shaping the social map in the city of Bengkulu, Dai also plays a role in empowering the general public and communities. This creates an attraction focused on community empowerment, carried out by migrant Da`I in religious, educational, and economic spheres. The purpose of this research is to study and analyze community development carried out by migrant Da`I in the field of community empowerment, focusing on religion, education, and the economy. The research method used is qualitative with field research. The data collection process was carried out through in-depth interviews, observations, documentation studies, and literature reviews of the results of relevant previous research. The results of the study show that 1). Migrant Da`I in empowering religious communities includes: consultative, innovative, participatory da`wah, and social cohesion. 2) Migrant Da`I in community empowerment in the educational dimension includes: formal, non-formal, and informal education. 3). Migrant Da`I in community empowerment in the economic dimension includes: Active in financial institutions, program mentoring, mediator and facilitator, resource person for entrepreneurship training.